Locating the southern boundary of the East European Platform within the north-western Black Sea shelf according to gravimetric data - Kozlenko, M.V.; Kozlenko, Yu.V. (Geofizicheskiy Zhurnal, 2022)
The work is devoted to the problem of determining the position of the border of the East European Platform (EEP) and the Scythian Plate (SP), which is of great economic importance in dividing the north-western shelf of the Black Sea into more and less promising areas for hydrocarbons. An analysis of the allocation of the juncture of EEP and SP using 23 literature sources published from 1985 to 2020 was performed. The essential differences in drawing the relevant line by different authors are shown. A method for determining the position of the southern boundary of the EEP within the north-western shelf of the Black Sea is proposed, based on the integrated use of gravimetry data — characteristic features of the gravity field (Δgf.a.) and the results of systematic two-dimensional density modeling. The outcome of modelling allowed determining the position and nature of the EEP and SP junction in the section of the earth’s crust, which turned out to be a transcrustal fracture of the southern falling with angles of inclination from 83.5° to 85.5° in different parts of the shelf. According to calculations of the exit points of the faults on the basement surface superimposed on the scheme Δgf.a made it possible to identify the spatial position of the junction of EEP and SP and its extension outside the modeling area for the entire study area. It is established that this line has a zigzag character, changing direction at the intersection with submeridional faults. It is shown that the formation of the southern boundary of EPS was controlled, except for the submeridional component characteristic of EPS, by three other systems — latitude, directions NE-SW and NW-SE, which are observed for tectonic elements of SP in Pridobruzha and Crimea. The correctness of the determination of the boundary position by gravimetric data is confirmed by the results of seismic stratigraphy and thermometry previously obtained by other researchers.